Rearrange the equation (x-1)(x-1)(x-1)=y to solve for x.?

NetherCraft 0

Thanks for the answer

4 Answers

  • (x-1)^(3)=y

    Take the cube root of each side of the equation to setup the solution for x.

    (x-1)^(3*(1)/(3))=(y)^((1)/(3))

    Remove the perfect root factor (x-1) under the radical to solve for x.

    (x-1)=(y)^((1)/(3))

    Remove the parentheses around the expression x-1.

    x-1=(y)^((1)/(3))

    Expand the exponent ((1)/(3)) to the expression.

    x-1=(y^((1)/(3)))

    Remove the parentheses around the expression y^((1)/(3)).

    x-1=y^((1)/(3))

    Since -1 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 1 to both sides.

    x=1+y^((1)/(3))

    Move all terms not containing x to the right-hand side of the equation.

    x=y^((1)/(3))+1

  • ( x – 1 ) ³ = y

    ( x – 1 ) = y^(1/3)

    x = y^(1/3) + 1

  • (x – 1)^3 = y

    x – 1 = y^1/3)

    x = y^(1/3) + 1

  • (x – 1)^3 = y

    x – 1 = y^(1/3)

    x = y^(1/3) + 1

Also Check This  come si dice buon natale in cinese?..è urgente..grazie?

Leave a Reply

Your email address will not be published. Required fields are marked *